Changes in interpersonal violence and utilization of trauma recovery services at an urban trauma center in the United States during the COVID-19 pandemic: a retrospective, comparative study - Kevin Y. Zhu; Kristie J. Sun; Mary A. Breslin; Mark Kalina Jr.; Tyler Moon; Ryan Furdock; Heather A. Vallier (Journal of Trauma and Injury)
Purpose This study investigated changes in interpersonal violence and utilization of trauma recovery services during the COVID-19 pandemic. At an urban level I trauma center, trauma recovery services (TRS) provide education, counseling, peer support, and coordination of rehabilitation and recovery to address social and mental health needs. The COVID-19 pandemic prompted considerable changes in hospital services and increases in interpersonal victimization. Methods A retrospective analysis was conducted between September 6, 2018 and December 20, 2020 for 1,908 victim-of-crime patients, including 574 victims of interpersonal violence. Outcomes included length of stay associated with initial TRS presentation, number of subsequent emergency department visits, number of outpatient appointments, and utilization of specific specialties within the year following the initial traumatic event. Results Patients were primarily female (59.4%), single (80.1%), non-Hispanic (86.7%), and Black (59.2%). The mean age was 33.0 years, and 247 patients (49.2%) presented due to physical assault, 132 (26.3%) due to gunshot wounds, and 76 (15.1%) due to sexual assault. The perpetrators were primarily partners (27.9%) or strangers (23.3%). During the study period, 266 patients (mean, 14.9 patients per month) presented before the declaration of COVID-19 as a national emergency on March 13, 2020, while 236 patients (mean, 25.9 patients per month) presented afterward, representing a 74.6% increase in victim-of-crime patients treated. Interactions with TRS decreased during the COVID-19 period, with an average of 3.0 interactions per patient before COVID-19 versus 1.9 after emergency declaration (P<0.01). Similarly, reductions in length of stay were noted; the pre–COVID-19 average was 3.6 days, compared to 2.1 days post–COVID-19 (P=0.01). Conclusions While interpersonal violence increased, TRS interactions decreased during the COVID-19 pandemic, reflecting interruption of services, COVID-19 precautions, and postponement/cancellation of elective visits. Future direction of hospital policy to enable resource and service delivery to this population, despite internal and external challenges, appears warranted.